Antibacterial activity and mechanism of Litsea cubeba essential oil against food contamination by Escherichia coli and Salmonella enterica. Issue 4 (6th May 2020) - Mei, Canchao; Wang, Xue; Chen, Yicun; Wang, Yangdong; Yao, Feng; Li, Zicheng; Gu, Qing; Song, Dafeng
Abstract: Litsea cubeba essential oil (LC‐EO) has been reported as antibacterial agents, but there are few studies about its possible antibacterial mechanism. The antibacterial activities and the underlying mechanisms of LC‐EO against Escherichia coli O157: H7 and Salmonella enterica were investigated. The results showed that the LC‐EO was more effective against gram‐negative bacteria. The inhibition zone for E. coli O157: H7 and S. enterica were 3.1 ± 0.8 and 4.5 ± 0.6 mm, respectively. The minimum inhibitory concentration of LC‐EO against both bacteria was 0.9 μg/ml, while the minimum bactericidal concentrations were 4.5 and 9 μg/ml. Gas chromatography–mass spectrometry analysis confirmed that citral (86.8%) was the main component of LC‐EO. The results of a time–kill analysis illustrated that treatment with LC‐EO led to a rapid decrease in viable bacterial cell number. The release of electrolytes and nucleic acids from the bacterial cells increased with the dose of LC‐EO. Propidium iodide uptake revealed that LC‐EO caused cell membrane damage. Scanning electron and transmission electron microscopy showed that LC‐EO caused damage to the cell walls and membranes, resulting in cell deformation, atrophy, and large central voids. Thus, LC‐EO may provide the basis for the development of new natural food preservatives. Abstract : The main compounds of LC‐EO were citral and nerol. In the present study, gram‐negative bacteria had greater sensitivity to LC‐EO than gram‐positive bacteria. LC‐EO could lead to damage to the cell wall and membrane, resulting in the leakage of cell contents, such as electrolytes and nucleic acids, and eventual cell death.